Cobaltand nickel-containing enzyme constructs from the sequences of methanogens - Chellapandi P.; Balachandramohan J. (Вiopolymers and Cell, 2012)
Aim. The conserved domain of sequences revealed in methanogens is considered for designing enzymes among which the attention has been focused on the metalloenzymes showing evolutionary significances. Methods. Molecular evolution, molecular modelling and molecular docking methods. Results. Molecular evolutionary hypothesis has been applied for designing cobalt-containing sirohydrocholine cobalt chelatase and nickel-containing coenzyme F420 non-reducing hydrogenase from conserved domains encompassing metaland substrate-binding sites. It was hypothesized that if any enzyme has similar or identical conserved domain in its catalytic region, the construct can bring similar catalytic activity. Using this approach, the region which covers such functional module has to be modeled for yielding enzyme constructs. The present approach has provided a high likelihood to design stable metalloenzyme constructs from the sequences of methanogens due to their low functional divergence. The resulted enzyme constructs have shown diverse reaction specificity and binding affinity with respective substrates. Conclusions. It seems to provide a new knowledge on understanding the catalytic competence as well as substrate-specificity of enzyme constructs. The resulted enzyme constructs could be experimentally reliable as the sequences originally driven from methanogenic archaea.